2018
DOI: 10.1111/ger.12372
|View full text |Cite
|
Sign up to set email alerts
|

Oral care as a life course project: A qualitative grounded theory study

Abstract: The theory explains why the loss of a single tooth might be experienced as traumatic but also why older people adapt to their changing oral health. Oral health in older age represented a lifetime's investment in oral care. Future health policies should consider this lifetime investment when considering care for older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 45 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…We would suggest further intergenerational research on oral health practices to explore the significance of family relationships over the life course. Although all interviews could be read through the lens of connectedness, family relationships were not always the focus (see Gibson et al ., Forthcoming; Gibson et al , ). We have selected narratives in order to show how connectedness can work as an analytical tool.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We would suggest further intergenerational research on oral health practices to explore the significance of family relationships over the life course. Although all interviews could be read through the lens of connectedness, family relationships were not always the focus (see Gibson et al ., Forthcoming; Gibson et al , ). We have selected narratives in order to show how connectedness can work as an analytical tool.…”
Section: Resultsmentioning
confidence: 99%
“…However, several participants who had been employed in professional roles highlighted a disadvantaged background, which became part of their personal narrative of accessing the social world of dentistry (Gibson et al . ). In‐depth, audio‐recorded interviews were undertaken with all participants; 34 in the participant's home, and the rest in cafes or university buildings.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…But then if it became so expensive or I couldn't afford it or variables, usually has to do with the economics, I would have to have false teeth I suppose which I would loathe.While many participants in this study had worked in professional or managerial occupations, the potentially prohibitive cost of dental treatments was noted in several interviews, and two working-class participants recalled not going to the dentist for periods when it was too expensive. Previous research has identified the cost of dental treatment as a barrier to the use of oral health-care services among older people (Borreani et al ., 2010), so it is important to recognise the relatively high socio-economic status of the majority of our participants who did not feel excluded from the social world of organised dentistry and consumer oral care (Gibson et al , in press). Furthermore, working to maintain one's own teeth at a substantial cost, rather than having all one's teeth removed and replaced by dentures, could reflect an intergenerational shift in values.…”
Section: ‘Mouth Talk’mentioning
confidence: 99%
“…There are a range of interesting papers in this issue but I wish to highlight two of these: Oral care as a life course project: A qualitative grounded theory study , by Gibson, Kettle, Robinson, Walls and Warren; and Developmental regulation of lifelong dental experiences and beliefs in Guangzhou and Hong Kong, by MacEntee, Wong, Chi, Lo, Minichiello, Soheilipour and Mariño . Oral health and oral disease are complex with many factors potentially influencing outcomes including broader social, political and economic factors .…”
mentioning
confidence: 99%